2003
DOI: 10.1023/a:1022133219353
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Promotes Growth and Angiogenesis in Polyoma Middle T Transgenic Mouse Mammary Tumor Explants

Abstract: SummaryEstrogen is important for breast carcinogenesis and the majority of breast cancers maintain hormone dependency. Estrogen has the ability to stimulate both breast epithelial cell growth and angiogenesis, and a well-characterized in vivo cancer model where these functional interactions can be studied is lacking. We demonstrate estrogen dependent angiogenesis, growth in vivo, and proliferation in vitro, in explants from polyoma middle T transgenic mouse mammary tumors. Thus, in addition to genetic similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 17 publications
6
48
0
Order By: Relevance
“…injections of ketamine/xylazine, oophorectomised (OVX), and 3-mm pellets containing 17 b-oestradiol, 0.18 mg 60-d À1 release, or placebo pellets (Innovative Research of America, Sarasota, Florida, USA) were implanted subcutaneously in the animal's back 7 days before tumour induction. The pellets provide continuous release of oestradiol at serum concentrations of 150 -250 pM, confirmed previously by serum analysis (Dabrosin et al, 2003b), which is in the range of physiologic levels during the estrous cycle in mice. At 1 week after surgery, MCF-7 cells (5 Â 10 6 cells in 200 ml PBS) were injected s.c. on the right hind side flank.…”
Section: Animals and Oophorectomy Of Micesupporting
confidence: 64%
“…injections of ketamine/xylazine, oophorectomised (OVX), and 3-mm pellets containing 17 b-oestradiol, 0.18 mg 60-d À1 release, or placebo pellets (Innovative Research of America, Sarasota, Florida, USA) were implanted subcutaneously in the animal's back 7 days before tumour induction. The pellets provide continuous release of oestradiol at serum concentrations of 150 -250 pM, confirmed previously by serum analysis (Dabrosin et al, 2003b), which is in the range of physiologic levels during the estrous cycle in mice. At 1 week after surgery, MCF-7 cells (5 Â 10 6 cells in 200 ml PBS) were injected s.c. on the right hind side flank.…”
Section: Animals and Oophorectomy Of Micesupporting
confidence: 64%
“…As shown by us, and others, these breast tumors express the ER during the early stage of cancer and decrease ER expression at later stages (29,30). Harvesting tumor tissue at early stages results in estrogen-dependent cancer growth in the syngeneic recipient mouse, as previously described (27,30). Tumors were established in oophorectomized mice with/without estrogen supplementation and with estrogen together with fulvestrant as described above.…”
Section: Murine Breast Cancer Modelsmentioning
confidence: 86%
“…However, other mechanisms may also contribute in the higher response of oestradiol treated tumours. We have recently shown that oestradiol-treated PyMT tumours used in this experiment have a higher microvessel count compared with tumours at the same size grown in OVX mice with placebo supplement (Dabrosin et al, 2003). This could affect the access of the tumour cells to the immune cells, that is, oestradiol-treated tumours have higher blood flow and are thereby more available to the immune system.…”
Section: Discussionmentioning
confidence: 86%
“…These tumours express the ER and E2 stimulates tumour cell proliferation in vitro and tumour growth in vivo (Dabrosin et al, 2003). Moreover, E2 enhances tumour angiogenesis in vivo (Dabrosin et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation